PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, KEBIJAKAN DEVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010 â 2013) - Muhamad Irfan, 12.05.51.0144; Irsad, Moch. (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Firm Size, Growth, Devidend Policy, and Profitability to Firm Value in an industrial manufacturing company that go public on the Indonesian Stock Exchange. The sampling method inthis study using purposive sampling method with the studyperiod of 2010 to 2013. The data used in this research is data from manufacturing companies that meet the selection criteria. The analytical method used in this study is multiple regresion analysis.The multiple regression shows that Firm Size, Devidend Policy, and Profitability have significant positive effect on Firm Value, while Growth havenât significant positive effect on Capital Structure. Adjusted R Square value of 0,848 can illustrate that the dependent variable is explained by the independent variable variabelitas for 84,8%%, while 15,2% are influenced by the other variables. Keywords: Firm Value, Firm Size, Growth, Devidend Policy, and Profitability